FATIGUE BEHAVIOR OF WELDED STRUCTURES - Claudiu BABIS; Oana CHIVU; Andrei DIMITRESCU; Gabriel IACOBESCU; Anamaria FEIER; Augustin SEMENESCU (Fiabilitate şi Durabilitate)
Fatigue is a phenomenon consisting of the accumulation of stresses and deformations that cause cracking and sometimes dismantling or even destruction of structures as a consequence of applying variable loads over time as intensity and position ( load cycles). The applied loads have values below the yield limit of the material from which the structure is made. These loads having values below the yield limit, under static stresses, would not have the effect of causing the fracture to fail. The paper aims is to present the basic mechanism of fatigue fracture by fatigue on the one hand and on the other hand presents some experimental researches regarding the evaluation of the quality of fillet welded joints of “GiurgeniVadulOii” bridge.